Cardiac autoantibodies promote a fibrotic transcriptome and reduced ventricular recovery in human myocarditis - Myers, Jennifer M.; Sandel, Clayton; Alvarez, Kathy; Garman, Lori; Wiley, Graham; Montgomery, Courtney; Gaffney, Patrick; Stavrakis, Stavros; Fairweather, DeLisa; Bruno, Katelyn A.; Zhao, Yan Daniel; Cooper, Leslie T.; et al. (Frontiers in Immunology, 2025)
Myocarditis leads to dilated cardiomyopathy (DCM) with one-third failing to recover normal ejection fraction (EF 50%). Our previous studies have supported a Th17 autoimmune pathogenesis where IL17A and IL-6 are elevated in myocarditis patients who do not recover normal EF. In the non-recovered group, autoantibody mechanisms of pathogenesis in myocardial injury and systolic dysfunction are not fully understood. Furthermore, in our myocarditis cohort, cardiac myosin (CM) autoantibodies (AAbs) were elevated and cross-reactive with the β−adrenergic receptor (βAR). Here we studied cross-reactive CM/βAR serum AAbs and human myocarditis-derived monoclonal antibodies (mAbs) to define their potential pathogenic mechanisms and to identify unique human CM epitopes associated with non-recovery in a longitudinal (n=41) cohort. Elevated CM IgG AAbs in the non-recovered phenotype correlated with reduced EF and poor outcomes. Human CM epitopes unique to the non-recovered phenotype shared strong amino acid sequence homology with extracellular loops of βARs and supported molecular mimicry and cross-reactivity between CM and βAR. Myocarditis-derived IgG and human mAb 2C.4 activated protein kinase A (PKA) in an IgG, CM, and βAR-dependent manner in H9c2 heart myoblast cell line, and transcriptomic analysis revealed mAb 2C.4 induced fibrosis pathways which were highly similar pathways seen with isoproterenol, a beta receptor agonist. Our data translate into new mechanistic insights from our small longitudinal group of myocarditis/DCM patients and into potential therapeutic targets and biomarkers for future studies.